Análisis lógico de la jurisprudencia sobre el empresario comercial en Costa Rica - González Solano, Gustavo (2018)
This paper analyzes the entrepreneur figure as a natural person under Commercial Law in Costa Rica. This concept and current jurisprudential accuracies are examined under the scope of the Commercial Code and the Law on Promotion and Effective Consumer Protection.